Characteristics of Coastal Farmers in Kulon Progo Regency - Yuhan Farah Maulida; Subejo Subejo (Agro Ekonomi, 2020)
The study explored the characteristics of coastal farmers in Kulon Progo Regency. It emphasized the issues of the socio-economical arrangements of farmers in marginal and resource-poor area and the access of farmers to productive capital. The research will contribute to development practitioners and policymakers in prescribing the context-specific policies and programs. In doing so, the research aimed at exploring the characteristics of coastal farmers in aspects like age, educational level, farming experiences and monthly income, as well as uncover their access to productive capital. The data came from a survey carried out using a questionnaire-based field interview, which adopted and used a simple random sampling method to select 60 respondents. The result of this research showed that the average age of coastal farmers is 43.2 years. In majority, farmers went to school for 10-12 years or were graduated from high school. Besides, 86.53% of the farmers had more than 10-year experience, which indicated that farming in coastal areas was profitable. The average monthly income of coastal farmers was 6 million rupiahs during peak season. Chili, the most profitable crop, contributed as the primary source of income, mostly when the selling price was high. Access to land, livestock, transportation (motorbike), extension services, internet and informal institution were considered high and very high, while access to four-wheeled transportation, credit and formal institution (farmers’ group) were medium and low.